PANDANGAN NAWAWI TENTANG PENGAMBILAN KEPUTUSAN STRATEGIS FUNDAMENTAL - Renita, Renita; Wandi, Didi (Desanta Publisher, 2023)
This abstract provides a concise summary of the key elements of Nawawi's perspective on strategic management. The abstract includes the issue and focus of the discussion, the objectives, the methodology or approach, and the outcomes of the discussion. Issue and Focus: The focus of this discussion is on Nawawi's definition of strategic management as a large-scale planning process aimed at achieving long-term future goals. It emphasizes the significance of fundamental decisions made by top leaders in organizations. Objectives: The objective of this paper is to explore and elucidate Nawawi's concept of strategic management, highlighting its orientation towards long-term future outcomes. It also aims to emphasize the crucial role of effective planning in enabling organizations to optimize their operations and achieve strategic objectives. Methodology or Approach: This discussion employs a descriptive approach to analyze Nawawi's perspective on strategic management. It involves a careful examination of his definition, highlighting the fundamental decisions made by top leaders and the importance of large-scale planning. Results: Nawawi's viewpoint underscores the significance of strategic management as a means to facilitate effective organizational interaction and the production of high-quality goods, services, and operational plans. It emphasizes the need for optimization aligned with the achievement of strategic goals and organizational objectives